Mixing work with pleasure my life at Studio Ghibli - Suzuki, Toshio 1948 August 19- (Japan library (Shuppan Bunka Sangyō Shinkō Zaidan), 2018)
"Toshio Suzuki has devoted himself to Studio Ghibli for some thirty years, producing such world-renowned animated classics as "Princess Mononoke" and "Spirited away." Early in his career he met the two genius directors Hayao Miyazaki and Isao Takahata and gained their confidence. Working with these two inimitable directors, he experiences the joys and sorrows of filmmaking, and he continues today to guide the studio. Based on his innate inquisitive nature and the accumulated resources of thirty years, Suzuki has recounted in this book the story not only of Miyazaki and Takahata but also the other figures working at Studio Ghibli or in connection with it"--Dust jacket.